PSO based Direct Numerical Solution Method for Fluid Flows with Thermal Convection - Dr. H. K Suhas, Antariksha Verma (International Journal of Advanced Science and Technology, 2020)
As a critical number of modern applications and characteristic procedures, those are comprised of moving the particles in thick fluid flows, the ongoing investigations to demonstrate, reproduce and assess the elliptic particle sedimentation with the thermal convection suggests the various challenges. As the particles are free, it allows to move them around the area randomly which makes the problem more severe for the existing Direct Numerical Solution (DNS) elliptic particle sedimentation with the thermal convection proposed the novel DNS solution using the Particle Swarm Optimization (PSO) to improve the accuracy and minimize the error rates while estimation the solutions in multi-grid problem-solver model of Finite Element Fictitious Boundary Method (FEM-FBM). The PSO based multi-grid FEM-FBM called PFEM-FBM proposed as Direct Numerical Solution (DNS) to simulate and validate fluid flows with thermal convection. The PFEM-FBM method used to illuminate the congruity, energy, and warmth conditions effectively. The simulations using PFEM-FBM conducted using the two distinctive experiments. In the principal case, we re-enacted and approved the impacts of the thermal property of the fluid, for instance, thermal augmentation and thermal scattering on the sedimentation of an elliptic atom. The after effects of the research are validated using the simulation outcomes with recent techniques at the end.